If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(4x) = (x + 1) Remove parenthesis around (4x) 0.5 * 4x = (x + 1) Multiply 0.5 * 4 2x = (x + 1) Reorder the terms: 2x = (1 + x) Remove parenthesis around (1 + x) 2x = 1 + x Solving 2x = 1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2x + -1x = 1 + x + -1x Combine like terms: 2x + -1x = 1x 1x = 1 + x + -1x Combine like terms: x + -1x = 0 1x = 1 + 0 1x = 1 Divide each side by '1'. x = 1 Simplifying x = 1
| -1=13+a | | 256=8(7+8x)+8 | | X+1-5=3 | | 2+y/2=0 | | -5(y-1)= | | 9w^4-16t^2= | | x-0.8x=0.2x | | 10n=-90 | | 35=-10(x-2)+5 | | -21=-5n-2n | | 7v^2-v-6= | | -9(2z-7)=-26.5-4z | | ((U^-5/3*v^-1/2)^1/4)/U^-2*v^7/4*v^4/3))^3/2 | | 10w^2-5w-25=0 | | 1/5x-2=13/25-.07x | | -2x(8x-1)=114 | | (2x-7)=(2x+9) | | 2-3(x+4)=87 | | (4q+9)=(2q-1) | | (10+m)=5 | | 7b^2=6 | | 11+3x-7=6x+5 | | 5n^2+7n-14= | | 3.5x+8.5x=-19.5 | | 6r^2-4=-66 | | 8x+7-3x=2x-34 | | x-3÷2=x/5 | | -26.5-7.5c=4.5(8c+8.5) | | 22x+120=-34 | | x^2-3x^1/4-4 | | 7w+2=3w+9k | | 6x+3=3(x+7) |